Determining the place of libraries on the public agenda in Bulgaria - Rusinova, Evgeniya (Qualitative and Quantitative Methods in Libraries, 2019)
In the process of adapting of libraries to the dynamically changing environment, extremely relevant among the Bulgarian Library College, becomes the question of their place on the public agenda. The situation in the library sphere in the country requires a clear answer what is the attitude of the authorities, the media and the public towards the problems of libraries - their financing, the construction of new library buildings, creating conditions for encouraging their activity. These questions are subject to intense discussion in the specialized library press and in various scientific conferences. The questions about the public vision of libraries and their future, of libraries as "third place" on the agenda of the individual and others become more recent. The main problem, related with the clarification of the attitudes of different audiences (users and non-users) as well as the place of libraries on the public agenda, is the need for relevant information about the attitudes of different public and professional circles to libraries. This raises highly the question of the need to conduct various quantitative and qualitative researches. They are the only means of gathering information about the priorities of different public environments to respond what is the attitude towards the libraries and their activities, and where libraries are in the priorities of society. The observations over the Bulgarian practice show the existence of certain difficulties in analyzing the regard of the public, related to the nature of the information about the public attitudes which is available in the libraries. This indicates conducting of systematic surveys of individual segments of the audiences with purpose to answer what the public libraries can provide to the society to satisfy their different needs. Some preliminary observations of the public moods show, that especially in the small settlements, libraries have a significant potential to become an important place on the agenda of the individual by satisfying his needs for information and social contacts. The conducted separate quantitative and qualitative researches confirm the possibility of transforming the libraries into the small settlements into public- informational centers. The practice of using quantitative and qualitative method to examine the library audiences gives a possibility to extend the range of other activities that libraries conduct: cultural programs, self-education programs, lifelong learning, etc.